The Gurungs and Their Lhosar Festival - Kafle, Dol Raj (Humanities and Social Sciences Journal, 2022)
This study makes an attempt to trace the history and identity of the Gurungs who have been living, most densely in the districts of Gandaki province. In order to provide clear information about the physical constitution, the nature of the race belonging to this ethnic group has also been discussed. The study also tries to explore some aspects of Gurungs identity, particularly their identity as indigenous and ethnic people of Nepal given the fact that the Gurungs have been living in Nepal since ancient times. In doing so, the study delves deeper into the Gurung tradition of celebrating Lhosar festival as a New Year, exploring its origin and development. The objective of this study is to clarify what race the Gurungs belong to, where and when they entered Nepal and how it is linked with the way they celebrate the Lhosar festival. The major finding of the study is that the Gurungs are of Mongol race, who entered into Nepal from Tibet in ancient times and among the various Lhosars celebrated in Nepal, Tola Lhosar is celebrated by the Gurungs.